2007
DOI: 10.1002/jlcr.1434
|View full text |Cite
|
Sign up to set email alerts
|

Determining transition state structure using kinetic isotope effects

Abstract: Kinetic isotope effects (KIEs) have been found to be the most powerful tool available to physical organic chemists for determining the mechanism of reactions and for estimating the structure of their transition states. Various types of KIEs including primary-leaving group-, nucleophile-, and a-carbon KIEs and secondary alpha-and beta-deuterium KIEs are introduced. The factors that affect the magnitude of each of these KIEs are covered in some detail. Finally, the use of these KIEs to determine the mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 44 publications
3
15
0
2
Order By: Relevance
“…We, however, have lately reported that KIE values in reactions of the Pt(II) complex [PtMe 2 (2,2 0 -bipyridine)] with CH 2 RX reagents (in which R ¼ H [14], CH 3 [13], or Ph [16]) are significantly dependent on R and a high value is obtained when R is CH 3 or Ph. The latter cases have been described [13,16] as the presence of bulkier alkyl halides and creation of more room for the CaÀH(D) out-of-plane bending vibration [34]. We therefore have come to the conclusion that in oxidation addition reactions of organoplatinum(II) complexes with alkyl halides, nature of the Pt complex has a minor influence, while that of bulkiness of the alkyl halides has a significant influence on the resulting KIE values.…”
Section: Resultsmentioning
confidence: 95%
“…We, however, have lately reported that KIE values in reactions of the Pt(II) complex [PtMe 2 (2,2 0 -bipyridine)] with CH 2 RX reagents (in which R ¼ H [14], CH 3 [13], or Ph [16]) are significantly dependent on R and a high value is obtained when R is CH 3 or Ph. The latter cases have been described [13,16] as the presence of bulkier alkyl halides and creation of more room for the CaÀH(D) out-of-plane bending vibration [34]. We therefore have come to the conclusion that in oxidation addition reactions of organoplatinum(II) complexes with alkyl halides, nature of the Pt complex has a minor influence, while that of bulkiness of the alkyl halides has a significant influence on the resulting KIE values.…”
Section: Resultsmentioning
confidence: 95%
“…The physical origin of KIEs is a complex subject and the theory has advanced steadily over the years [6][7][8][9]. This topic will be discussed elsewhere in this special issue.…”
Section: Brief Kinetic Isotope Effect Methodology and Terminologymentioning
confidence: 99%
“…Adding to these ideas is the isotope effect which is one of the most powerful techniques available to determine the structure of the transition state (Westaway, 2007). The Hammond postulate theorizes that intermediates of a unimolecular reaction that are similar in energy to the transition state are also structurally similar.…”
Section: Isotope Effectsmentioning
confidence: 99%